Neonatal bilateral adrenal hemorrhage and adrenal insufficiency accompanied by Subgaleal hematoma: a case report with brief review of literature - Golnaz Ghazizadeh Esslami; Atousa Moienafshar (BMC, 2022)
Abstract Background Neonatal adrenal hemorrhage (NAH) is an almost infrequent phenomenon (0.2-0.55%). Mechanical compression and alterations of venous pressure during delivery are considered the most probable explanations. Approximately 10% of the cases might have bilateral involvement. Clinical symptoms include abdominal mass, poor feeding, vomiting, prolonged jaundice, and anemia. Subgaleal hemorrhage (SGH) is one of the most clinically remarkable and potentially hazardous postnatal cranial injuries. Case presentation An early-term Iranian male neonate who was born through spontaneous vaginal delivery and experienced shoulder dystocia was diagnosed with bilateral NAH leading to adrenal insufficiency requiring glucocorticoid and mineralocorticoid supplementation. The SGH and jaundice were other postnatal complications. Serial monthly abdominal and brain ultrasound revealed complete regression of lesions after 70 days. However, after 16 months, the neonate has been still treated with hydrocortisone and fludrocortisone for the adrenal insufficiency diagnosis. He has a lower limit weight for age; however, developmental milestones have been appropriate for age. Discussion and conclusion Adrenal hemorrhage and SGH should be examined and looked for, particularly with proven evidence of difficult delivery and asphyxia in at-risk newborns. Clinical and ultrasound follow-up is mandatory for the assessment of hemorrhage resolution and conservative management. The early detection and treatment of adrenal insufficiency by laboratory examination is strongly recommended in bilateral cases. Furthermore, the early recognition of postnatal SGH to prevent clinical and neurological outcomes seems essential.